2021
DOI: 10.1002/aic.17143
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulations of enantiomeric separations as an interfacial process in HPLC

Abstract: Since chromatographic separation is a dynamic process, with the interactions between the drug and the chiral stationary phase mediated by the solvent, no single interacting structure, such as could be found by minimizing the energy, could possibly describe and account for the ratio of residence times in the chromatographic column for the enantiomeric pair. We describe the use of explicit-solvent fully atomistic molecular dynamics simulations, permitting all the interactions between the atoms constituting the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 85 publications
0
10
0
Order By: Relevance
“…With the aim of understanding the molecular bases of enantioseparation processes performed in chromatography, the interest toward the application of computational tools in this field have been growing, and this interest is witnessed by numerous r e v i e w s p u b l i s h e d o n t h i s t o p i c r ecently. [57][58][59]565,1076,1077,1080,1378,1379 In most cases, molecular modelling is integrated into multidisciplinary study involving experimental techniques such as NMR and IR spectroscopy, XRD, and microcalorimetry with the aim of exploring chiral recognition by using orthogonal methods. The main objective of modelling chromatographic enantiodifferentiation is to gain precious information on the shape of the molecules, their dynamic features, and interaction capability.…”
Section: Computation-based Modelling Of Enantioseparation Processes A...mentioning
confidence: 99%
“…With the aim of understanding the molecular bases of enantioseparation processes performed in chromatography, the interest toward the application of computational tools in this field have been growing, and this interest is witnessed by numerous r e v i e w s p u b l i s h e d o n t h i s t o p i c r ecently. [57][58][59]565,1076,1077,1080,1378,1379 In most cases, molecular modelling is integrated into multidisciplinary study involving experimental techniques such as NMR and IR spectroscopy, XRD, and microcalorimetry with the aim of exploring chiral recognition by using orthogonal methods. The main objective of modelling chromatographic enantiodifferentiation is to gain precious information on the shape of the molecules, their dynamic features, and interaction capability.…”
Section: Computation-based Modelling Of Enantioseparation Processes A...mentioning
confidence: 99%
“…We have discussed the factors that need to be considered in designing the simulation system and described other examples of MD simulations of chiral separations involving other types of chiral selectors, such as those (Whelk O1, polyproline, and others) that are covalently bonded to the inner surfaces of a porous solid support, as well as cyclodextrins chemically anchored to silica support. 47 In summary, we have reviewed several examples of how MD simulations can act as a powerful tool for computational screening studies that help determine feasibility of new materials in industrial applications and narrowing down choices prior to testing them experimentally. We have also noted several instances in which these simulations can provide an increased molecular-level understanding of unexpected or puzzling experimental results.…”
Section: Chiral Separationsmentioning
confidence: 99%
“…Such an on-the-fly model may lead to insufficient sampling between polymer selector and chiral enantiomers. As an improvement, they constructed a more realistic model which included four polymer chains and an amorphous silica slab, which best describes the molecular structure of the CSP surface [110][111][112]. Special cares have been taken to ensure the final model of ADMPC on amorphous silica still maintains the correct polymer structure in the presence of solvent.…”
Section: Molecular Modeling Applied To Enantioseparationsmentioning
confidence: 99%
“…Note that, although naringenin is mentioned here, it not a unique case. Previous studies have revealed several other drugs, including valsartan, benzoin, and thalidomide, that have similar molecular recognition when passing through a column coated with the ADMPC selector [110][111][112].…”
Section: Molecular Modeling Applied To Enantioseparationsmentioning
confidence: 99%
See 1 more Smart Citation